Metabolomic profiling from leaves and roots of tomato (Solanum lycopersicum L.) plants grown under nitrogen, phosphorus or potassium-deficient condition. (December 2015) - Sung, Jwakyung; Lee, Suyeon; Lee, Yejin; Ha, Sangkeun; Song, Beomheon; Kim, Taewan; Waters, Brian M.; Krishnan, Hari B.
Highlights: Metabolites were identified in leaves and roots of N, P or K-deficient tomato plants. Mineral deficiency led to substantial increase in the level of soluble carbohydrates whereas significant decrease in amino acids and organic acids. N, P or K deficiency resulted in drastic decrease in α- keto glutarate concentrations in leaves while in huge increase in roots. N or K-deficiency induced alternative carbohydrate, raffinose family oligosaccharides, biosynthesis. Abstract: Specific metabolic network responses to mineral deficiencies are not well-defined. Here, we conducted a detailed broad-scale identification of metabolic responses of tomato leaves and roots to N, P or K deficiency. Tomato plants were grown hydroponically under optimal (5 mM N, 0.5 mM P, or 5 mM K) and deficient (0.5 mM N, 0.05 mM P, or 0.5 mM K) conditions and metabolites were measured by LC–MS and GC–MS. Based on these results, deficiency of any of these three minerals affected energy production and amino acid metabolism. N deficiency generally led to decreased amino acids and organic acids, and increased soluble sugars. P deficiency resulted in increased amino acids and organic acids in roots, and decreased soluble sugars. K deficiency caused accumulation of soluble sugars and amino acids in roots, and decreased organic acids and amino acids in leaves. Notable metabolic pathway alterations included; (1) increased levels of α- keto glutarate and raffinose family oligosaccharides in N, P or K-deficient tomato roots, and (2) increased putrescine in K-deficient roots. These findings provide new knowledge of metabolic changes in response to mineral deficiencies.